Stratigraphic Observations of Laterites in Pakistan and Oscillation and Movement of the Eurasian and Indian Blocks - Shah, S.H.A. (Journal of Himalayan Earth Sciences, 1984)
The laterite beds in Pakistan are found in isolated zones of outcrops but are spread over a wide area in the country. They can be divided stratigraphically into four age groups: Upper Devonian of Chitral district; Jurassic of Punjab and Baluchistan; Cretaceous-Paleocene of Punjab, Baluchistan and Sind; and Oligocene of Sibi. Laterites are also found as thin layers or ferrogenous coating in the Siwalik group of rocks. The mode of formation of the laterites indicates condition of sub-aerial weathering or oxidation. It has been observed that rocks rich in ferromagnesim minerals on oxidation gave rise to thicker beds of laterites having higher percentage of iron. Some interesting information regarding the movement of plates has been provided by these laterite layers when studied on regional scale.